AHMED BASIONY: MEDIA ARTIST OR MARTYR? - KHOLEIF, OMAR (Afterimage)
The article discusses the work of the Egyptian media artist Ahmed Basiony and how it has been appropriated following his murder on January 28, 2011 during the Egyptian revolution. The author argues that Basiony's death has led to an increased interest in his work and in Egyptian media art. Following his death, the Egyptian pavilion at the Venice Biennale was dedicated to his work. Titled "Amhed Basiony: 30 Days of Running in Place," the pavilion was curated by the Egyptian artist Shady El Noshokaty.